Recent advances in the direct transformation of propargylic alcohols to allenes. Issue 23 (11th October 2021) - Du, Sha; Zhou, An-Xi; Yang, Ruchun; Song, Xian-Rong; Xiao, Qiang
Abstract : This review summaries a view of the advances in the direct transformation of propargylic alcohols to functionalized allenes. Abstract : Allenes are the simplest class of cumulenes, possessing unique physical and chemical properties. These structural units are widely used as valuable synthetic intermediates in organic synthesis, as well as the key skeletons of many natural products, biologically active molecules, and pharmaceutical compounds. In recent decades, the development of synthetic methodologies for the synthesis of allenes by direct transformation of propargylic alcohols has attracted considerable attention among organic chemistry researchers. In this review, we focus on recent advances in the direct transformation of propargylic alcohols to allenes. These transformations can be divided into four categories according to their reaction types: (1) reactions with transition metal catalysis; (2) reactions involving carbocation intermediates; (3) reactions that are metal hydride (base)-mediated; and (4) reactions involving oxa-propargylic intermediates.